Reduced acute toxicity and improved efficacy from intensity-modulated proton therapy (IMPT) for the management of head and neck cancer - McKeever, Matthew R.; Sio, Terence T.; Gunn, G. Brandon; Holliday, Emma B.; Blanchard, Pierre; Kies, Merrill S.; Weber, Randal S.; Frank, Steven J. (Chinese Clinical Oncology; Vol 5, No 4 (August 18, 2016): Chinese Clinical Oncology (Proton Therapy-Guest Editors: Minesh Mehta, Arpit Chhabra), 2016)
Cancers in the head and neck area are usually close to several critical organ structures. Traditional external-beam photon radiation therapy unavoidably exposes these structures to significant doses of radiation, which can lead to serious acute and chronic toxicity. Intensity-modulated proton therapy (IMPT), however, has dosimetric advantages that allow it to deposit high doses within the target while largely sparing surrounding structures. Because of this advantage, IMPT has the potential to improve both tumor control and toxicity. To determine the degree to which IMPT can reduce toxicity and improve tumor control, more randomized trials are needed that directly compare IMPT with intensity-modulated photon therapy. Here we examine the existing evidence on the efficacy and toxicity of IMPT for treating cancers at several anatomic subsites of the head and neck. We also report on the ability of IMPT to reduce malnutrition, and gastrostomy tube dependence and improve patient-reported outcomes (PROs).